Features of Protein-Peptide and Carbohydrate Composition of Supernatants From Tenebrio Molitor Larvae After Cold Acclimation - Gulevsky, Aleksandr K.; Tretiak, Diana V. (Problems of Cryobiology and Cryomedicine, 2016)
The paper describes the chromatographic studies on the molecular-mass distribution of proteins and peptides of supernatants, derived from Tenebrio molitor larvae during cold acclimation. Supernatants of non-acclimated larvae of T. molitor had the highest amount of peptide fractions. It has been shown that cold-acclimated T. molitor larvae comprised the low-molecular peptide fractions with MW of (540 Â± 20) â€“ (2.255 Â± 85) Da, and high-molecular peptides with MW of (4.675 Â± 225) â€“ (6.595 Â± 550) Da were characteristic for non-acclimated larvae. The content of sugars and polyols in supernatants of cold-acclimated and non-acclimated T. molitor larvae was determined. It has been found that glucose concentration in non-acclimated T. molitor larvae was in 1.34 times higher than in cold-acclimated ones. Ðcclimated T. molitor larvae had more hydrophilic and less hydrophobic proteins as compared to non-acclimated ones. As well it has been established that non-acclimated T. molitor larvae had low concentrations of polyols (sorbitol and mannite), which were absent in acclimated insects. Probl Cryobiol Cryomed 2016; 26(4): 322â€“330